The influence of social media motivation and parasocial interaction on attitudinal and behavioral engagement among social media users - Pornsakulvanich, Vikanda; Tongnok, Thomtong (Humanities, Arts and Social Sciences Studies, 2022)
This study had two main purposes: to explore the relationships between social media motivation, parasocial interaction, and attitudinal and behavioral engagement, and to investigate any differences in gender and age group responses in terms of parasocial interaction. Survey research was used to study participants’ social media motives and behaviors. This study used purposive sampling to gather the data from social media users who used social media platforms and followed their favorite media figures on one of the social media, which included Facebook, Instagram, YouTube, Twitter, and Line. The total number of participants was 744. Overall, the results indicated the reasons people use social media the most were as follows: relationship maintenance, relaxation, new friendship, to pass time, entertainment, and peer influence. In addition, the results showed that those who used social media for relationship maintenance, relaxation, to pass time, entertainment, peer influence, and parasocial interaction were more likely to have attitudinal engagement with their favorite media personalities. Moreover, those who used social media for relaxation, entertainment, peer influence, and parasocial interaction were more likely to have behavioral engagement with their favorite media personalities. The results also indicated that younger groups were more likely to engage in parasocial interaction than those who were older. However, there were no gender differences found with regard to parasocial interaction.